3D Facial morphology in children affected by spinal muscular atrophy type 2 (SMAII). (16th September 2019) - Pucciarelli, Valentina; Gibelli, Daniele; Mastella, Chiara; Bertoli, Simona; Alberti, Katia; De Amicis, Ramona; Codari, Marina; Dolci, Claudia; Battezzati, Alberto; Baranello, Giovanni; Sforza, Chiarella
Summary: Objectives: The main objective of this study was to assess the three-dimensional facial characteristics of children affected by spinal muscular atrophy (SMA), a severe muscular disorder characterized by hypotonia, areflexia, weakness, and respiratory impairment. Materials/Methods: Stereophotogrammetric facial scans from 22 SMA type II patients aged 2–7 years were obtained. Data were analysed using both inter-landmark distances and principal component analysis and compared with data collected from matched control subjects. Results: Patients had wider transverse facial diameters, but smaller biocular width. Middle and lower anterior face heights were increased, whereas the mandibular ramus was shorter, with a reduced posterior-to-anterior face height ratio. Facial width-to-length ratio was reduced. In the sagittal plane, mandibular body length, and facial divergence were increased, whereas the gonial angles were decreased. In the horizontal plane, lower facial convexity was greater in patients, whereas mandibular convexity was smaller. Patients had smaller and down-slanted eye fissures, with a larger and more vertically developed nose. Limitations: This study assessed a relatively small number of patients, due to the rare frequency of SMA type II. Conclusions/Implications: SMA type II children possess peculiar facial alterations that may be due to the altered muscular activity. As feeding problems may derive also by malocclusion and masticatory muscular alterations, a detailed assessment of the craniofacial individual alterations should be considered in the standards of care of these patients.